2016
DOI: 10.1080/15596893.2016.1214806
|View full text |Cite
|
Sign up to set email alerts
|

Social participation of families with children with autism spectrum disorder in a science museum

Abstract: This article describes a qualitative research study undertaken as a collaboration between museum and occupational therapy researchers to better understand museum experiences for families with a child or children impacted by autism spectrum disorder (ASD). Inclusion for visitors with ASD is an issue that museums are increasingly considering, and the social dimension of inclusion can be particularly relevant for this audience. The construct of social participation, used in occupational therapy, provides a promis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 16 publications
0
23
0
1
Order By: Relevance
“…They reported that environmental features helped facilitate social participation of families' visits such as "interactive exhibits that were multi-sensory", "spacious exhibit halls with many options for engagement", and "clear signage related to wayfinding or sensory information" (Lussenhop et al, 2016, p. 129). They also mentioned the benefits of signage and sensory related information that informed visitors of areas with loud noises which allowed families to make an informed decision on whether they want to enter certain exhibits or not (Lussenhop et al, 2016). This research is one of the few studies which discusses some aspects of wayfinding and associated environmental elements that may help and benefit visitors with ASD when planning to go to a museum.…”
Section: Identifying Existing Support Systems and Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that environmental features helped facilitate social participation of families' visits such as "interactive exhibits that were multi-sensory", "spacious exhibit halls with many options for engagement", and "clear signage related to wayfinding or sensory information" (Lussenhop et al, 2016, p. 129). They also mentioned the benefits of signage and sensory related information that informed visitors of areas with loud noises which allowed families to make an informed decision on whether they want to enter certain exhibits or not (Lussenhop et al, 2016). This research is one of the few studies which discusses some aspects of wayfinding and associated environmental elements that may help and benefit visitors with ASD when planning to go to a museum.…”
Section: Identifying Existing Support Systems and Gapsmentioning
confidence: 99%
“…A similar study by Lussenhop et al (2016) aimed to understand the museum experience of children with ASD in collaboration with occupational therapy researchers. The authors highlight key factors in their findings associated with social participation.…”
Section: Identifying Existing Support Systems and Gapsmentioning
confidence: 99%
“…Additionally, Lussenhop et al. (2016) identified that clear exhibit signage which informed families of any loud or bright exhibits may be of benefit. Not all activities may need new or adapted signage, but an assessment of program labels and signage requiring modification has the potential to improve the quality of one’s SSP program.…”
Section: Program Development and Descriptionmentioning
confidence: 99%
“…For our SSP, registration was particularly important to create an accessible environment of reduced noise and crowd size (Lussenhop et al., 2016) a critical sensory consideration (Silverman & Tyszka, 2017). Based on our experience, additional considerations for identifying an event cap could also include factoring in registration attrition.…”
Section: Program Development and Descriptionmentioning
confidence: 99%
“…Research partnerships bring developmental scientists into museums; these scientists can engage families and museum staff to discuss findings on child development with individuals who could most benefit. Prior research on research-museum partnerships showed that parents of children who participated in a research exhibit reported positive experiences, that they learned something new, and found the research to be relevant to their own lives and the museum experience (Lussenhop et al, 2013(Lussenhop et al, , 2016. However, this feedback may have been driven by demand characteristics, given that participating families were recruited by indicating a desire to provide museum feedback and that interviews were conducted in person with museum staff and the researchers.…”
Section: Introductionmentioning
confidence: 99%